Airway Smooth Muscle Hypercontractility in Asthma. (18th March 2013) - Berair, Rachid; Hollins, Fay; Brightling, Christopher
Abstract : In recent years, asthma has been defined primarily as an inflammatory disorder with emphasis on inflammation being the principle underlying pathophysiological characteristic driving airway obstruction and remodelling. Morphological abnormalities of asthmatic airway smooth muscle (ASM), the primary structure responsible for airway obstruction seen in asthma, have long been described, but surprisingly, until recently, relatively small number of studies investigated whether asthmatic ASM was also fundamentally different in its functional properties. Evidence from recent studies done on single ASM cells and on ASM-impregnated gel cultures have shown that asthmatic ASM is intrinsically hypercontractile. Several elements of the ASM contraction apparatus in asthmatics and in animal models of asthma have been found to be different from nonasthmatics. These differences include some regulatory contractile proteins and also some components of both the calcium-dependent and calcium-independent contraction signalling pathways. Furthermore, oxidative stress was also found to be heightened in asthmatic ASM and contributes to hypercontractility. Understanding the abnormalities and mechanisms driving asthmatic ASM hypercontractility provides a great potential for the development of new targeted drugs, other than the conventional current anti-inflammatory and bronchodilator therapies, to address the desperate unmet need especially in patients with severe and persistent asthma.